1984
DOI: 10.1104/pp.75.4.902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Defoliant Thidiazuron on Ethylene Evolution from Mung Bean Hypocotyl Segments

Abstract: The effect of the defoliant thidiazuron (N-phenyl-N'1,2,3-thiadiazo1-5- (2,18), it is important to understand the biochemical mechanism(s) by which TDZ enhances its production. Etiolated mung bean hypocotyls have been used extensively as a model system for evaluating the effects ofmany compounds that either enhance ' Mention of trademark or proprietary product does not constitute a guarantee or warranty of the product by the United States Department of Agriculture and does not imply its approval to the exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…In etiolated mung bean hypocotyl segments, a marked synergism was found between kinetin and calcium ions (7). Other studies using this same tissue found only a marginal effect of calcium ions on TDZ-induced ethylene production (13). This type of marginal response to external calcium was also found in the present study (Table II).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In etiolated mung bean hypocotyl segments, a marked synergism was found between kinetin and calcium ions (7). Other studies using this same tissue found only a marginal effect of calcium ions on TDZ-induced ethylene production (13). This type of marginal response to external calcium was also found in the present study (Table II).…”
Section: Discussionsupporting
confidence: 76%
“…studies found a 6 h lag period in kinetin-induced ethylene production in etiolated mung bean hypocotyl segments (7). Previous studies in this laboratory have found a readily measurable increase in ethylene production from etiolated mung bean hypocotyl segments within 2 h of TDZ treatment (13). In cotton leaves, no increase in ethylene evolution could be detected until 7 to 8 h following TDZ treatment (Table III).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Similarly, TDZ has been shown to promote shoot regeneration with an efficiency comparable to or greater than that of cytokinins (7,9). The effectiveness of TDZ to inhibit stomatal closure and to stimulate ethylene production in bean is also consistent with the properties of a cytokinin (6), although the pattern of the lag period in elevation of ethylene production by TDZ-treated mung bean tissue was similar to that induced by an auxin (19). However, in our study, both exogenous BAP and IAA were replaced by TDZ.…”
Section: Methodsmentioning
confidence: 67%